Achievements and prospects for the synthesis of poly(meth)acrylimide foams. Stage of the thermal imidisation of polymer precursors. Issue 1 (January 2021) - Kazantsev, Oleg A; Shirshin, Konstantin V; Kornienko, Pavel V; Sivokhin, Alexey P
The review summarises the trends in the development of research on the synthesis of polymethacrylimides (PMIs) and polyacrylimides by the method of intramolecular thermal imidisation of (meth)acrylic polymers. Along with the widely used industry variant of PMI foam of the 'Rohacell' series based on bulk copolymers of methacrylonitrile and methacrylic acid, intensive research on alternative variants began after 2005. This review describes the main and side reactions when using polymer precursors of different structures as well as the effect of precursor composition and structure on the properties of the resulting poly(meth)acrylimides. It has been shown that the achievements of the last 15 years provide a basis for reducing the cost of poly(meth)acrylimides which will significantly expand the areas and scale of their application.